If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 6(2x + -3) = 4 + 7x Reorder the terms: 3x + 6(-3 + 2x) = 4 + 7x 3x + (-3 * 6 + 2x * 6) = 4 + 7x 3x + (-18 + 12x) = 4 + 7x Reorder the terms: -18 + 3x + 12x = 4 + 7x Combine like terms: 3x + 12x = 15x -18 + 15x = 4 + 7x Solving -18 + 15x = 4 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -18 + 15x + -7x = 4 + 7x + -7x Combine like terms: 15x + -7x = 8x -18 + 8x = 4 + 7x + -7x Combine like terms: 7x + -7x = 0 -18 + 8x = 4 + 0 -18 + 8x = 4 Add '18' to each side of the equation. -18 + 18 + 8x = 4 + 18 Combine like terms: -18 + 18 = 0 0 + 8x = 4 + 18 8x = 4 + 18 Combine like terms: 4 + 18 = 22 8x = 22 Divide each side by '8'. x = 2.75 Simplifying x = 2.75
| -10-4x+(-4)=70 | | -12r=-5 | | 2(2-4)=3(z-4) | | 3w^3/4w*9/w | | 3/4c=12 | | 5x+6x+3+8=8x+5+2x | | 7x^2-400=0 | | x/5=3y+7 | | 2377960+26T=2067959+125T | | 10x^2+8.5X+5=0 | | 10Y=40 | | x+[x-4]+4[x-4]=52 | | -4+12t=100 | | 3x+2=-4x+23 | | y+2x=-3x+1 | | 9p+2=9+8p | | 2(2y-4)=12x | | 2(2y-4)=12x | | 2e-3.1=1.7 | | y=3x^3-3x^2 | | y-11=7 | | 2377960+26T=3000000 | | 7x+9y+17z=19y+13x+4z | | =24x^2-48x+16 | | 22x+80=30x | | 11/3x=22 | | 17-9m=1m-23 | | -0.25x-(-1.5)=10 | | 5(5x-5)=50 | | 7/4x=22 | | 16t^4-56t^3+72t^2-40t-3=0 | | X+(x-4)+4(x-4)=52 |